Evaluation of smartphone user experience: identification of key evaluation items and their relationships. (2018) - Kim, Kwang-Jae; Kim, Hyun-Jin; Yim, Jinho; Heo, Jun-Yeon; Kim, Min-Jun; Shin, Seungchul; Ahn, Hyo-in
User experience (UX) refers to the comprehensive experience of a user when interacting with a product. UX plays an essential role in enhancing the value of a product in the current marketplace. Compared with a feature phone, a smartphone enables users to significantly extend the usage of the device. Given the impressive market growth of the smartphone, evaluating its UX has become important in its development process. However, studies on the evaluation of smartphone UX are limited. Thus, we conducted a study on smartphone UX from the perspective of UX evaluation. At first, a total of 329 evaluation items for smartphone UX were identified based on the literature review and user study, and they were categorised as product, context, and emotion items. Then, to utilise the items in the three categories, we proposed a two-phase procedure for UX evaluation consisting of identification of key items (phase 1) and identification of causal relationships among the key items (phase 2). As a case study, seven key contexts were identified and the relationships of key items were statistically identified based on 461 user data. The results of this study can help practitioners evaluate their smartphone UX in a systematic manner.